TERMINATION OF PREGNANCY USING COMBINATION OF CABERGOLINE AND CLOPROSTENOL IN A QUEEN - RANGASAMY, S; JEMIMAH, RACHEL; SRIDEVl, P; JOSEPH, CECILIA (The Indian Journal of Animal Reproduction, 2023)
A 11 month old domestic short hair queen at 40 days of gestation was subjected to medical termination of pregnancy using a combination involving antiprolactin drug, Cabergoline per os and prostaglandin analogue, Cloprostenol intramuscular administered once daily.Three foetuses were expelled on the 4th day of treatment. Ultrasonographic examination on 5th day revealed empty gestational sac suggesting that the termination was completed.